Head and Neck Cancer Reconstruction with or without Internal Lining Using Various Flaps in a Tertiary Care Hospital: Head and Neck Cancer Reconstruction: Internal Lining Using Various Flaps - Dogar, Muhammad Razzaq; Anwar, Zubair; Khatri, Vijay Kumar; Mahar, Ghulam Shabir; Waheed, Abdul; Mushtaq, Allah Bux (Pakistan Journal of Health Sciences, 2025)
Reconstructive surgeries of the head and neck with or without the use of internal lining must be thoroughly evaluated for post-operative complications and functional outcomes unclear phrasing. Objectives: To compare the surgical outcomes, complication rates, and functional outcomes of head and neck cancer reconstruction surgeries performed with or without internal lining using various flap techniques in a Tertiary Care Hospital setting. Methods: This one-year prospective comparative study at Al-Tibri Medical College included 139 head and neck cancer patients undergoing resection and reconstructive surgery with or without internal lining. Data on demographics, tumor, surgical, and postoperative outcomes were analyzed using SPSS version 23.0, applying appropriate statistical tests with significance set at p<0.05. Results: From 139 patients, operative time was significantly longer in Group A (with flap and internal lining) than in Group B (p<0.001). Postoperative complications were more common in Group A, with higher rates of wound infection (15.7% vs. 5.8%, p=0.04) and overall complications (28.6% vs. 11.6%, p=0.01). Functional outcomes favored Group B, with significantly better swallowing (82.6% vs. 55.7%, p=0.007) and speech intelligibility (79.7% vs. 60%, p=0.04). Hospital stays over 7 days were more common in Group A (35.7% vs. 14.5%, p=0.009). The need for secondary intervention was higher in Group A, but not statistically significant. Overall, Group B demonstrated fewer complications and better postoperative functional recovery. Conclusions: Head and neck reconstruction without internal lining resulted in fewer complications, shorter hospital stay, and better functional recovery than reconstruction with internal lining. Careful patient selection can optimize outcomes and surgical efficiency.